Nanotechnology and natural killer cell immunotherapy: synergistic approaches for precise immune system adjustment and targeted cancer treatment in gastrointestinal tumors - Kang, Xiwen; Li, Danyang; Sun, Rui (Frontiers in Medicine, 2025)
Gastrointestina (GI) tumors are a major contributor to global cancer-related illness and death, marked by their rapid growth, late detection, and resistance to standard treatments. NK cells, key cytotoxic components of the innate immune system, show promise in immunotherapy due to their ability to target tumor cells without requiring antigen presentation. Nonetheless, their effectiveness against gastrointestinal tumors is constrained by issues such as insufficient tumor penetration, brief survival in the body, and suppression by the immunosuppressive tumor microenvironment (TME). Meanwhile, nanotechnology has transformed cancer treatment by offering methods for precise drug delivery, immune system modulation, and improved bioavailability. Combining NK cells with specially designed nanoparticles (NPs) has created a powerful system with amplified cooperative anti-tumor effects, improving the targeting of tumors, activation of NK cells, and their endurance, while also allowing for control over the tumor immune microenvironment in both space and time. This thorough review investigates the complex interaction between the immunobiology of NK cells and the design of nanomaterials, specifically in the context of gastrointestinal tumors. Key areas of focus include nanoparticle-assisted engineering of NK cells, cytokine delivery, biomimetic disguise, reprogramming of the TME, and targeting of tumors specifically. We critically assess preclinical and emerging clinical evidence that supports the effectiveness of these combined therapies, analyze related safety and translational challenges, and suggest forward-looking approaches involving gene editing, innovative stimulus-responsive systems, and AI-assisted therapeutic personalization. In conclusion, this review presents the combined NK-NP approach as a promising new frontier in the advancement of personalized, immune-guided treatments for gastrointestinal cancers.